Etika Komunikasi Islam ETIKA KOMUNIKASI ISLAM ANTARA GURU DAN MURID DALAM KITAB TAZKIRAH AS-SAMI‘ WA AL-MUTAKALLIM FI ADAB AL-‘ALIM WA AL-MUTA‘ALLIM - Irham Dongoran; Daryanto Setiawan; Ahmad Rifandy (Bashirah, 2022)
This study aims to determine the form of Islamic communication ethics of students to teachers used by Ibn Jama'ah and as a solution to solving problems of communication between students and teachers. This type of research is library research with a descriptive qualitative approach, the primary data source is the book Tazkirah As-Sami‘ Wa Al-Mutakallim Fi Adab Al-‘Alim Wa Al-Muta‘Allim”", From the results of this study, namely the ethics of Islamic communication between students and teachers, occurs in two places, namely in lessons and outside lessons and there are 22 forms of Islamic communication ethics and Qaulan Karima dominates almost all of the other Qaul in every place, and there is no Qaulan Baliga which used by Ibn Jama'ah